Detection of novel germline mutations for breast cancer in non‐BRCA1/2 families. (14th July 2015) - Aloraifi, Fatima; McDevitt, Trudi; Martiniano, Rui; McGreevy, Jonah; McLaughlin, Russell; Egan, Chris M.; Cody, Nuala; Meany, Marie; Kenny, Elaine; Green, Andrew J.; Bradley, Daniel G.; Geraghty, James G.; et al.
<x xml:space="preserve">Abstract</x> The identification of the breast cancer susceptibility genes BRCA1 and BRCA2 enhanced clinicians' ability to select high‐risk individuals for aggressive surveillance and prevention, and led to the development of targeted therapies. However, BRCA1/2 mutations account for only 25% of familial breast cancer cases. To systematically identify rare, probably pathogenic variants in familial cases of breast cancer without BRCA1/2 mutations, we developed a list of 312 genes, and performed targeted DNA enrichment coupled to multiplex next‐generation sequencing on 104 'BRCAx' patients and 101 geographically matched controls in Ireland. As expected, this strategy allowed us to identify mutations in several well‐known high‐susceptibility and moderate‐susceptibility genes, including ATM ( 5%), RAD50 ( 3%), CHEK2 ( 2%), TP53 ( 1%), PALB2 ( 1%), and MRE11A ( 1%). However, we also identified novel pathogenic variants in 30 other genes, which, when taken together, potentially explain the etiology of the missing heritability in up to 35% of BRCAx patients. These included novel potential pathogenic mutations in MAP3K1, CASP8, RAD51B, ZNF217, CDKN2B‐AS1, and ERBB2, including a splice site mutation, which we predict would generate a constitutively active HER2 protein. Taken together, this work extends our understanding of the genetics of familial breast cancer, and supports the need to implement hereditary multigene panel testing to more appropriately orientate clinical management.